The Contribution Of Learning Culture To Increasing Organizational Innovation Capacity - Thomas Abellio; Nabila Septia; Sherly Wahyuni; Sholiha Elmujadida Nugraha; Kaltsum Ulima Syafiqah Khairiyah; Kiki Cahaya Setiawan (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2025)
A learning culture is a crucial foundation for adaptive, creative, and innovative organizations. This study examines the contribution of a learning culture to an organization's innovation capacity, emphasizing how collective values, norms, and practices influence the ability to generate, develop, and implement new ideas. In a dynamic global environment, organizations are required not only to be efficient but also to transform through systematic and reflective learning. Findings indicate that a strong learning culture creates a work environment open to feedback, cross-functional collaboration, and calculated risk-taking. Organizations with a strong learning culture are better able to manage knowledge, adapt quickly, and enhance employee competencies. This culture also strengthens social cohesion, a sense of ownership, and motivation to contribute to the innovation process. Key factors such as transformational leadership, a reward system for new ideas, and technological support and knowledge infrastructure strengthen these relationships. Thus, a learning culture is not simply a social asset but a strategic driver in building sustainable innovation capacity and long-term competitive advantage.